Innate Immunity and Breast Milk - Cacho, Nicole Theresa; Lawrence, Robert M. (Frontiers in Immunology, 2017)
Human milk is a dynamic source of nutrients and bioactive factors; unique in providing for the human infant’s optimal growth and development. The growing infant’s immune system has a number of developmental immune deficiencies placing the infant at increased risk of infection. This review focuses on how human milk directly contributes to the infant’s innate immunity. Remarkable new findings clarify the multifunctional nature of human milk bioactive components. New research techniques have expanded our understanding of the potential for human milk’s effect on the infant that will never be possible with milk formulas. Human milk microbiome directly shapes the infant’s intestinal microbiome while the human milk oligosaccharides (HMOs) drive the growth of these microbes within the gut. New techniques such as genomics, metabolomics, proteomics and glycomics are being employed to describe this symbiotic relationship. An expanded role for antimicrobial proteins/peptides (AMPs) within human milk in innate immune protection is described. The unique milieu of enhanced immune protection with diminished inflammation results from a complex interaction of anti-inflammatory and anti-oxidative factors provided by human milk to the intestine. New data supports the concept of mucosal-associated lymphoid tissue and its contribution to the cellular content of human milk. Human milk stem cells (hMSCs) have recently been discovered. Their direct role in the infant for repair and regeneration is being investigated. The existence of these hMSCs could prove to be an easily harvested source of multi-lineage stem cells for the study of cancer and tissue regeneration. As the infant’s gastrointestinal tract and immune system develop there is a comparable transition in human milk over time to provide fewer immune factors and more calories and nutrients for growth. Each of these new findings opens the door to future studies of human milk and its effect on the innate immune system and the developing infant.